Sex hormones and pain: the evidence from functional imaging - Vincent, K; Tracey, I (Springer, 2010)
There is a substantial body of epidemiological and clinical evidence suggesting that the sex hormones, particularly estradiol and progesterone, play a role in pain. Behavioral studies have not been useful in understanding the relationship between sex hormones and pain perception, and certainly have not helped to elucidate the mechanisms by which such effects may be mediated. This review aims to address the additional insights functional imaging has given us into the role of sex hormones in pain. Functional imaging techniques and experimental designs are discussed before the literature investigating specific questions relating to hormones and pain is reviewed. Finally, we conclude by considering how results of studies imaging the influence of sex hormones in related areas such as emotion and cognition also may inform our understanding of this complex area.